Front Cover: Serum semaphorin 4C as a diagnostic biomarker in breast cancer: A multicenter retrospective study. Issue 12 (23rd December 2021) - Wang, Ya; Qiao, Long; Yang, Jie; Li, Xiong; Duan, Yaqi; Liu, Jiahao; Chen, Shaoqi; Li, Huayi; Liu, Dan; Fang, Tian; Ma, Jingjing; Li, Xiaoting; et al.
Abstract : The cover image is based on the Original Article Serum semaphorin 4C as a diagnostic biomarker in breast cancer: A multicenter retrospective study by Qinglei Gao et al., https://doi.org/10.1002/cac2.12233 .